Should Consumption Sub-Aggregates Be Used to Measure Poverty? - Christiaensen, Luc; Ligon, Ethan; Pave Sohnesen, Thomas (World Bank, Washington, DC, 2020)
Frequent measurement of poverty is challenging, as measurement often relies on complex and expensive expenditure surveys that try to measure expenditures on a comprehensive consumption aggregate. This paper investigates the use of consumption "sub-aggregates" instead. The use of consumption sub-aggregates is theoretically justified if and only if all the Engel curves are linear for any realization of prices. This is very stringent. However, it may be possible to empirically identify certain goods that happen to have linear Engel curves given prevailing prices, and when the effect of price changes is small, such a sub-aggregate might work in practice. The paper constructs such linear sub-aggregates using data from Rwanda, Tanzania, and Uganda. The findings show that using sub-aggregates is ill-advised in practice as well as in theory. This raises questions about the consistency of the poverty-tracking efforts currently applied across countries, since obtaining exhaustive consumption measures remains an unmet challenge.